Russian Jewish immigrants in the United States: The adjustment of their English language proficiency and earnings in the American Community Survey - Barry R. Chiswick; Nicholas Larsen (Institute for the Study of Labor (IZA), 2012)
Compared to other immigrants to the United States, recent Jewish immigrants from the former Soviet Union have achieved high levels of English language proficiency and earnings. They experience disadvantages in both dimensions at arrival, but because of steeper improvements with duration in the United States, they reach parity or surpass the English proficiency and earnings of other immigrants. This pattern is seen in the most recent data, the American Community Survey, 2005 to 2009, which is studied here, but also in earlier censuses (1980-2000). The Russian Jews, whether male or female, have higher levels of schooling and English proficiency. Moreover, they appear to secure greater earnings payoffs in the US labor market from their schooling, their labor market experience in the US, and their proficiency in English. What is perhaps remarkable is that the Russian Jewish immigrants from the late 19th and early 20th centuries (1881 to 1920's) also experienced high levels of human capital accumulation and economic success (measured by earnings or occupational attainment). And their US-born children achieved even greater successes compared to other native-born children. This is not emerging from a highly selective immigrant population. The Russian Jewish migration is a mass migration influenced, in part, by refugee motivations. This leads to the obvious but still unanswered question: What is it about the Jews of the Former Russian Empire/Soviet Union that has resulted in their high levels of success in the United States over the past 25 years?
Keywords: F22; J61; J31; J24; 330; Soviet Jews; immigrants; earnings; schooling; English language; proficiency; American Community Survey; Migranten; Juden; Russen; Mehrsprachigkeit; Englisch (Sprache); Einkommen; USA